Viscosity and Excess Volume of Anisaldehyde-Nitrobenzene at 303.15 K, 313.15 K and 323.15 K - BASKARAN, R.; KUBENDRAN, T.R. (Asian Journal of Chemistry, 2010)
Densities (ρ) and viscosities (η) have been measured for the binary liquid mixture of anisaldehyde + nitrobenzene over the entire composition range at 303.15, 313.15 and 323.15 K. Excess molar volume (VE) and viscosity deviations (Δη), have been calculated. The appropriate models were used to correlate the measured properties. It was found that in all cases, the experimental data obtained fitted very well with the values correlated by the corresponding models. The molecular interactions existing between the components were discussed.